2019
DOI: 10.1108/ijicc-05-2019-0047
|View full text |Cite
|
Sign up to set email alerts
|

Multi-criteria decision making method based on improved cosine similarity measure with interval neutrosophic sets

Abstract: Purpose The fuzziness and complexity of evaluation information are common phenomenon in practical decision-making problem, interval neutrosophic sets (INSs) is a power tool to deal with ambiguous information. Similarity measure plays an important role in judging the degree between ideal and each alternative in decision-making process, the purpose of this paper is to establish a multi-criteria decision-making method based on similarity measure under INSs. Design/methodology/approach Based on an extension of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…Hence, Equations (25), (31), and (35) are used in comparison to determine their relationship with α j of Equation (26). By the same observation, it is found that Equations (27), (32), and (36) are related to β j of Equation (28).…”
Section: Further Discussion For Aggregation Operatorsmentioning
confidence: 85%
See 2 more Smart Citations
“…Hence, Equations (25), (31), and (35) are used in comparison to determine their relationship with α j of Equation (26). By the same observation, it is found that Equations (27), (32), and (36) are related to β j of Equation (28).…”
Section: Further Discussion For Aggregation Operatorsmentioning
confidence: 85%
“…In Equations (25) and (27), the most natural approach f ðxÞ = x is applied by us. Meanwhile, in Equations (31) and (32), Ye and Fu [7] used f ðxÞ = tan ðπx/4Þ, and in Equations (35) and (36) For a similarity measure, say Sim, Simð0Þ = 1, and Simð1Þ = 0 are ideal, such as in Equations (25), (27), (31), and (32) and then abstractly expressed in Equations (33) and (34), researchers use 1 − ∑ m j=1 w j f ðα j Þ or 1 − ∑ m j=1 w j f ðβ j Þ.…”
Section: Further Discussion For Aggregation Operatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The decision making refers to the human activities that rank the alternatives and select the optimal ones [26,38,39,55]. It is extremely common in our daily life and national industrial development [10,13,23].…”
Section: Introductionmentioning
confidence: 99%
“…Choquet integral-based aggregation operator has been applied [8,9], and it has improved the weakness of simple weighted sum method. For example, if we consider a set of four alternatives {x 1 , x 2 , x 3 , x 4 } where each alternative x i is evaluated with three criteria to maximize: x 1 = (18; 10; 10), x 2 = (10,18,10), x 3 = (10,10,18), x 4 = (14,11,12), in truth, the alternative x 4 is not a selected solution with a weighted sum operator, however this alternative is the most balanced alternative and it would likely be a good option. This shortcoming has been overcome by defining a new operator using Choquet integral to make fuzzy measurement [6].…”
Section: Introductionmentioning
confidence: 99%